UPAYA BADAN USAHA MILIK DESA (BUM DESA) MEKAR SARI DESA RAMBAH BARU DALAM MERAIH BEBAS TUNGGAKAN SIMPAN PINJAM TAHUN 2015 - Ridwan "; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is motivated by the success achieved by BUM Desa Mekar Sari  Rambah Baru village in winning an award certificate as BUM Desa which is free from savings and loan arrears since it started from UED-SP in 2010 to become BUM Desa. The award certificate was received by BUM Desa Mekar Sari on January 27, 2016 in the annual accountability meeting of BUM Desa Mekar Sari. This is certainly inseparable from the efforts and support provided by the government and community participation in BUM Mekar Sari Village.This study aims to describe the efforts made by the government in mobilizing BUM Mekar Sari Village to achieve free savings and loan arrears in 2015 and describe the efforts made by the people of Rambah Baru Village in moving BUM Mekar Sari Village to achieve free savings and loan arrears in 2015. The method used in this research is a descriptive study with a qualitative approach. The type of research data is primary data and secondary data. Data collection techniques in this study were interviews and documentation. The data analysis technique used is descriptive qualitative data analysis.The results showed that in the implementation of empowerment carried out by the government in mobilizing BUM Mekar Sari Village, Rambah Baru Village in achieving free savings and loan arrears through human development, environmental development and institutional development were running optimally. However, for business development is still not running optimally. This is due to the still undeveloped BUM Desa business unit and the lack of BUM Desa capital. And the impact felt by the community from the provision of loan funds by BUM Desa is the development of the community's economy. So that the community participates in using the services provided by BUM Desa and has high awareness and responsibility in returning loans provided by BUM Desa. Keywords: Free of Arrears, Human Development, Business Development, Community Development, Institutional Development